Walking home - Walters, Eric, 1957- (Doubleday Canada, 2014)
"Thirteen-year-old Muchoki and his younger sister, Jata, can hardly believe what has become of their lives. Only weeks ago, they lived in a bustling Kenyan village, going to school, playing soccer with friends, and helping at their parents' store. But sudden political violence has killed their father and destroyed their home. Now, Muchoki, Jata, and their ailing mother live in a tent in an overcrowded refugee camp. By day, they try to fend off hunger and boredom. By night, their fears about the future are harder to keep at bay. And then the unthinkable happens: their mother dies and they are left orphaned. Driven by a desperate optimism, Muchoki and Jata set off on what seems like an impossible quest: to walk over a hundred miles across Kenya in search of their last remaining family"--Back cover.